ANALYSIS OF THE INFLUENCE OF PRICE, HALAL AWARENESS, HALAL LABELS ON THE DEMAND FOR HALAL FOOD AND BEVERAGE PRODUCTS IN TRUNOJOYO SQUARE, SAMPANG - Fitria, Anis; Sri Rahayuningsih, Eni (Universitas Islam Lamongan, 2024)
This study aims to analyze the effect of price, halal awareness, and halal labels on the demand for halal food and beverage products in Alun-alun Trunojoyo Sampang as an effort to increase halal awareness of the community, especially traders. Given that the first stage of mandatory halal is applied to food and beverage products, as well as service products until the final deadline, namely October 17, 2024. The variables used in this study are price, halal awareness, and halal labels. The sample in this study used a purposive sampling technique with the criteria, people who have purchased halal food and beverage products in the Alun-alun Trunjoyo Sampang area. The number of samples was 100 respondents. Data analysis used Multiple Linear Regression. The results of this study indicate that price has a negative effect on the demand for halal food and beverage products, while halal awareness and halal labels have a significant positive effect on the demand for halal products.